An integrated management strategy for acid mine drainage control of sulfidic tailings. (July 2022) - Mafra, Carolina; Bouzahzah, Hassan; Stamenov, Lachezar; Gaydardzhiev, Stoyan
Highlights: Feasibility of environmental desulfurization and cemented paste backfill. Leaching behavior of cemented paste backfill. Environmental benefits of cemented paste backfill. Environmental and economical benefits of integrated management strategy of mine tailings. Abstract: The oxidation of sulfide minerals releases acidic leachate enriched in sulfate, iron, and toxic metals and metalloids (e.g., As, Sb, Cu, Pb, Cd, Zn, Hg, etc.) known as acid mine drainage (AMD). This eco-hydrological hazard is imminent when mineralogical and geochemical analysis indicates that acid-generating (sulfides) overcome the acid-neutralizing (carbonate) minerals in the ore and mining waste. AMD represents a multifaceted problem faced by the mining industry. The most widespread management technique is to store the tailings into engineered impoundments and actively neutralize the acidity produced by the oxidation of the sulfide minerals by adding alkaline chemical agents. However, this method involves a constant and long-term commitment, elevated operational costs, and several geotechnical and environmental drawbacks. In a pre-mining stage, geological, geochemical, mineralogical, and textural characterization of the mine waste could guide proper and site-specific mining waste management. In this paper, we present an integrated strategy to reduce the acid mine drainage (AMD) potential of the Dundee Precious Metals Chelopech (DPM-Ch) tailings through a combination of environmental desulfurization and cemented paste backfill (CPB) – the latter one being already practiced on-site. In the proposed scenario, a desulfurization plant would be installed downstream to re-float the non-valuable reactive pyrite. The reactive pyrite concentrate would be combined with the CPB material, whereas the remaining tailings would be discharged at the tailings management facility (TMF). The lack of neutralizing gangue (NP of untreated tailings < 8 kg CaCO3 /t) precludes converting the tailings into non-acid generating. However, reducing nearly six times the amount of lime required to neutralize the acidity produced by pyrite oxidation was feasible without substantially increasing operational costs. Supporting the environmental benefits of combining desulfurization and backfill, an X-ray mapping of the CPB material revealed that this approach effectively encapsulates the reactive gangue, ultimately avoiding pyrite oxidation and leaching of heavy metals.